Combining Preconcentration Methods for the Determination of Lead and Nickel in Ambient Air by FAAS - Yaman, Mehmet; Erel, Ensar (Atomic Spectroscopy Press Ltd, 2012)
The main routes of human exposure to toxic trace metals for non-occupationally exposed individuals are inhalation and ingestion through diet. Because the absorption rates of metals by inhalation are significantly higher (up to 50-60%) than those by ingestion (between 3-10%), the determination of trace metals in ambient air samples is of special interest. In this study, three pre-concentration methods are combined for the determination of Pb and Ni in ambient air by FAAS. For this purpose, the PAR-loaded XAD-7, thiouresulphonamid polymeric resin, and cupferron-activated carbon systems that were optimized in the past were used sequentially, and the seasonal distributions of Pb and Ni in ambient air of Elazig City, Turkey, were determined. The obtained Pb and Ni concentrations are highly variable depending on the season and were found to be in the range of 18-61 ng m(-3) and 10.5-47 ng m(-3), respectively.
Keywords: Trace-Metal Concentrations; Flame Aas; Cadmium; Elements; Copper; Biomonitors; Vegetables; Enrichment; Manganese; Exposure